Trace Elements Status and Metallothioneins DNA Methylation Influence Human Hepatocellular Carcinoma Survival Rate - Udali, Silvia; De Santis, Domenica; Mazzi, Filippo; Moruzzi, Sara; Ruzzenente, Andrea; Castagna, Annalisa; Pattini, Patrizia; Beschin, Greta; Franceschi, Antonia; Guglielmi, Alfredo; Martinelli, Nicola; Pizzolo, Francesca; et al. (Frontiers in Oncology, 2021)
Background Mechanisms underlying hepatocellular carcinoma (HCC) development are largely unknown. The role of trace elements and proteins regulating metal ions homeostasis, i.e. metallothioneins (MTs), recently gained an increased interest. Object of the study was to investigate the role of promoter DNA methylation in MTs transcriptional regulation and the possible prognostic significance of serum trace elements in HCC. Methods Forty-nine HCC patients were enrolled and clinically characterized. Cu, Se, and Zn contents were measured by Inductively Coupled Plasma Mass Spectrometry in the serum and, for a subset of 27 patients, in HCC and homologous non-neoplastic liver (N) tissues. MT1G and MT1H gene expression in hepatic tissues was assessed by Real-Time RT-PCR and the specific promoter DNA methylation by Bisulfite-Amplicon Sequencing. Results Patients with Cu serum concentration above the 80th percentile had a significantly decreased survival rate (P < 0.001) with a marked increased hazard ratio for mortality (HR 6.88 with 95% CI 2.60–18.23, P < 0.001). Se and Zn levels were significantly lower in HCC as compared to N tissues (P < 0.0001). MT1G and MT1H gene expression was significantly down-regulated in HCC as compared to N tissues (P < 0.05). MTs promoter was hypermethylated in 9 out of the 19 HCC tissues showing MTs down-regulation and methylation levels of three specific CpGs paralleled to an increased mortality rate among the 23 patients analyzed (P = 0.015). Conclusions MT1G and MT1H act as potential tumor suppressor genes regulated through promoter DNA methylation and, together with serum Cu concentrations, be related to survival rate in HCC.